How do regions use indirect R&D support for their innovation activities? - Klímová, Viktorie (Univerzita Pardubice, 2018)
It is broadly accepted that innovation is an important source of competitiveness in developed regions and that research and development brings new knowledge that can be utilized for the development of new innovations. This paper deals with indirect support for research and development that is used for promotion of innovation activities in the Czech Republic. The aim of the article is to provide new empirical evidence on using of indirect support of research development for financing of innovation activities in Czech regions. The statistical data are analysed through descriptive statistics, cluster analysis and correlation analysis. It was observed that indirect R&D support is strongly concentrated in Prague and the Central Bohemian Region. The situation in the South Moravian Region is different, although this region has many common features with the former regions. The cluster analysis also revealed a group of regions with quite a high level of indirect support. These regions are not the innovation leaders, but they can be characterized by a strong industrial base.
Keywords: indirect support; tax incentives; research and development; innovation; region; R12; H25